2011
DOI: 10.1159/000327574
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro Examination of the Tendinous Inscription of the Human Semitendinosus Muscle

Abstract: The aim of this study was to examine the tendinous inscription (TI) of the human semitendinosus (ST) muscle using dissection (cadavers) and ultrasound (in vivo). Ultrasonography (US) scans were taken in 18 young males at rest and at maximum voluntary contraction (MVC). Further, the ST was dissected and removed from its origins in 10 cadaveric specimens (5 cadavers). The cadaveric long arm of the TI was 6.67 ± 0.64 cm (6.45 ± 1.21 in US) while the shorter arm was 2.39 ± 0.38 cm (1.99 ± 0.75 in US). The angle fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 69 publications
(61 reference statements)
3
38
0
Order By: Relevance
“…No differences in fascicle lengths between distal and proximal compartments were found, except for the most distal fascicles at both compartments ('fasc d ). Similar fascicles lengths within the two compartments (Wickiewicz et al 1983;Woodley & Mercer, 2005;Kellis et al 2012), as well as shorter fascicle lengths in the proximal compared with the distal compartment (Markee et al 1955), have been reported. However, comparison of the results between the present data and those of previous studies regarding differences in fascicle lengths within and between compartments is hampered by a lack of standardization of the location of the measured fascicles or differences in the dissection plane.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…No differences in fascicle lengths between distal and proximal compartments were found, except for the most distal fascicles at both compartments ('fasc d ). Similar fascicles lengths within the two compartments (Wickiewicz et al 1983;Woodley & Mercer, 2005;Kellis et al 2012), as well as shorter fascicle lengths in the proximal compared with the distal compartment (Markee et al 1955), have been reported. However, comparison of the results between the present data and those of previous studies regarding differences in fascicle lengths within and between compartments is hampered by a lack of standardization of the location of the measured fascicles or differences in the dissection plane.…”
Section: Discussionsupporting
confidence: 70%
“…; Woodley & Mercer, ; Kellis et al. ), as well as shorter fascicle lengths in the proximal compared with the distal compartment (Markee et al. ), have been reported.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors found SEM below 10%. In vivo, high intrarater and interrater reproducibility was reported to semitendinosus pennation angle (ICC > 0.83) (Kellis et al, 2011). This study is the first to describe the in vivo muscle thickness and fascicle length measurements reliability for the semitendinosus muscle using ultrasound.…”
Section: Discussionmentioning
confidence: 69%
“…The ST muscle is characterized by the presence of a tendinous inscription (TI), which consists of 2 arms that intersect along the midway of the muscle length. The inscription is highly visible on the ultrasound image, especially during changes in hamstrings length [29]. For this reason, we monitored the TI position during the SLR as an index of hamstring muscle−tendon extensibility [29] (Figure 1).…”
Section: Methodsmentioning
confidence: 99%